Case Report: Eosinophilic gastritis with pyloric stenosis in immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome - Yu, Ronghua; Xiao, Yongmei; Xu, Wuhen; Zhang, Ting; Wang, Yizhong; Hu, Hui (Frontiers in Pediatrics, 2022)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare X-linked recessive immunodeficiency caused by mutations in the forkhead box protein 3 (FOXP3) gene. IPEX is characterized by the onset of intractable diarrhea, type 1 diabetes mellitus (T1DM), and eczema in the early stages of life. Typical clinic triad for IPEX is not always seen. Here, we report a 15-year-old male patient with atypical IPEX syndrome complicated with severe eosinophilic gastritis (EG) and pyloric stenosis. The patient had noticeable eczema during the first year of life and had a history of food allergies. At age 3, the patient was diagnosed with EG, Helicobacter pylori (HP) infection, pyloric stenosis with recurrent vomiting, and failure to thrive. The patient did not respond to long-term symptomatic treatments in the following years, including methylprednisolone, proton pump inhibitors (PPI), L-glutamine and sodium gualenate granules, anti-HP therapy, and balloon dilation. At age 12, the patient received surgical interventions, including laparoscopic jejunostomy feeding tube placement, gastrojejunal anastomosis bypass, and jejunal-jejunal end-to-side anastomosis. Intractable diarrhea and T1DM were not present in the patient. At age of 14, the patient was diagnosed with IPEX syndrome due to a c.748-750del (p.Lys250del) mutation in the leucine zipper domain of the FOXP3 protein. The patient underwent matched sibling peripheral blood hematopoietic stem cell transplantation (HSCT) and showed good evolution after three months of HSCT. In summary, this case report provides information of an unusual gastrointestinal findings in IPEX syndrome, and highlights the needs for increased awareness and early diagnosis of IPEX syndrome is vital for improving the patient’s outcome.